Antimalarial activity of hydromethanolic extract and its solvent fractions of Vernonia amygdalina leaves in mice infected with Plasmodium berghei. (May 2019) - Bihonegn, Temesgen; Giday, Mirutse; Yimer, Getnet; Animut, Abebe; Sisay, Mekonnen
Background: Vernonia amygdalina Del. (Asteraceae) is reported to be traditionally used for the treatment of malaria. Based on folkloric repute of this plant in Ethiopian traditional medicine and crude extract-based ethnopharmacological studies conducted in few countries, this study was undertaken to evaluate the in vivo antimalarial activity of 80% methanol extract and its solvent fractions of the leaves of V. amygdalina in mice infected with Plasmodium berghei . Methods: A 4-day suppressive test was conducted on mice infected with P. berghei to find out antimalarial effect of chloroform, butanol and aqueous fractions obtained from the 80% methanol crude extract. In all the activity tests, mice were randomly assigned in five groups (three tests and two controls) of six animals in each and received respective treatments. Data were analyzed using one way analysis of variance followed by Tukey's post hoc test for multiple comparisons. Results: Acute oral toxicity test showed that all solvent fractions of the leaves of V. amygdalina revealed neither mortality nor overt signs of toxicity up to 2000 mg/kg. This study indicated that the percentage parasitemia suppression of 80% methanol extract was 32.47% (±2.65), 35.40% (±3.14) and 37.67% (±2.50) at 200, 400 and 600 mg/kg, respectively. All doses of the 80% methanol extract of V. amygdalina prolonged survival time and prevented weight loss and packed cell volume reduction in infected mice. All doses of chloroform and butanol fractions significantly suppressed parasitemia (p < 0.05), increased survival time (p < 0.05) compared to negative control and exhibited a significant reduction in rectal temperature (p < 0.05). All solvent fractions significantly prevented weight loss (p < 0.05) at all tested doses. The 80% methanol extract and chloroform and butanol fractions significantly (p < 0.05) prevented further reduction in rectal temperature of P. berghei- infected mice at all doses. Conclusion: The results of this study indicated that 80% methanol extract and solvent fractions of the leaves of V. amygdalina demonstrated promising antimalarial activity. The study corroborated the folklore use of this plant for the treatment of malaria in ethnomedicine in Ethiopia.